Effect of hybrid wollastonite with different nucleation and morphology on the crystallization and mechanical properties of polypropylene. (8th July 2018) - Ding, Qian; Zhang, Zishou; Dai, Xin; Li, Mei; Mai, Kancheng
Abstract : In order to prepare polypropylene (PP) composites with balanceable stiffness and toughness, hybrid wollastonite with different nucleation and morphology as fillers were added into PP matrix. Nucleation efficiency (NE), crystallization behavior and melting characteristics, as well as the mechanical properties of hybrid wollastonite‐filled PP composites were systematically investigated using differential scanning calorimetry, wide‐angle X‐ray diffraction, mechanical testing, and scanning electron microscopy, respectively. The results indicated that the NE of wollastonite with β‐nucleation is much higher than that of acicular wollastonite and ultrafine wollastonite with α‐nucleation, and eventually hybrid wollastonite‐filled PP composites mainly form β‐phase PP. Furthermore, there exists cooperative effect between the reinforcement of wollastonite of different morphology and the toughening of β‐phase, which can be effectively controlled through regulating the nucleating ability, morphology, and mass ration of hybrid wollastonite. POLYM. COMPOS., 40:E638–E646, 2019. © 2018 Society of Plastics Engineers